Życie poza heteronormą — "Pustostany", "Cukry" i "Czerwony młoteczek" Doroty Kotas - Lewińska, Karolina (Zagadnienia Rodzajów Literackich, 2024)
In this article, I refer to the concept of compulsory heterosexuality, characterized by such queer theorists as Adrienne Rich, Sara Ahmed, and Judith Butler. The norms created and popularised by heterosexual couples have a constant impact on the lives of non-heteronormative people, as shown by the example of heroines and narrators of Dorota Kotas’ works (Pustostany 2019, Cukry 2021, Czerwony młoteczek 2023). The strategies adopted towards forced heterosexuality may be based on assimilation — striving to adopt as much as possible — or anti-assimilation, opposing adjustment. I analyze Dorota Kotas’s novels in chronological order, as they were published, noting that issues related to non-heteronormativity are becoming an increasingly common topic in her works. The matter of non-cisgender identity, raised in her latest novel, seems just as important, since the very disruption of the gender binary makes it impossible to establish any kind of homonormativity — a concept treated by some as a direct response to heteronormativity. In the conclusion, I point out that the behavior of Kotas’ heroines clearly shows that it is impossible to escape heteronormativity — even if you oppose it, you exist in relation to the ruling power. This analysis could contribute to a deeper understanding of the mechanisms governing sexual normativity.